DETERMINANTS OF ORGANIC FOOD CONSUMPTION AMONG YOUNG ADULTS IN MALAYSIA: A CONCEPTUAL PAPER - Akma, Tuan Nor Zahrina Tuan Shahidil; Yasin, Nurul Hafizah Mohd; Ab Rashid, Ahmad Faezi (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2026)
Organic food consumption among young adults has attracted increasing scholarly and practical attention due to growing concerns over health, food safety, and environmental sustainability. However, existing empirical findings remain fragmented, with limited integration of psychological, social, and control-related determinants, particularly within emerging economies such as Malaysia. This limitation restricts a comprehensive understanding of the factors shaping organic food consumption behaviour among young consumers. Grounded in the Theory of Planned Behaviour (TPB), this conceptual paper proposes an extended framework that integrates attitude, subjective norms, and perceived behavioural control with additional constructs, namely health consciousness and environmental concern. By incorporating these contemporary sustainability-driven factors, the study advances TPB beyond its traditional scope to better reflect evolving consumer priorities. The proposed framework offers a more holistic explanation of organic food consumption by capturing the interplay between individual evaluations, social influences, and perceived constraints within the Malaysian context. This study contributes theoretically by extending TPB in an emerging economy setting and practically by providing insights for policymakers and marketers to design targeted interventions that promote sustainable and health-oriented consumption among young adults.